MEDICINAL POTENTIAL AND BIOECOLOGICAL CHARACTERISTICS OF LAMIACEAE SPECIES IN UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
The Lamiaceae family, commonly known as the mint family, comprises a vast array of plant species with significant medicinal, aromatic, and ornamental value. This article explores the bioecological properties of various medicinal species within the Lamiaceae family, particularly those found in Uzbekistan. The study emphasizes the importance of these species in local and industrial applications, highlighting their roles in traditional and modern medicine, food, and perfumery industries. Data were collected from various botanical texts, research articles, and field studies conducted in different regions of Uzbekistan. The bioecological properties, traditional uses, and current applications of these species were analyzed to provide a holistic understanding of their significance. Additionally, field observations and specimen collections were conducted to verify the presence and ecological characteristics of specific species. This comprehensive review aims to provide insights into the biodiversity, ecological significance, and potential applications of these plants, underscoring the need for their conservation and sustainable utilization.